PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP PENERAPAN PENGANGGARAN BERBASIS KINERJA PEMERINTAH PROVINSI BENGKULU - Fransisca, Fransisca; Saiful, Saiful; Aprila, Nila (JURNAL FAIRNESS, 2018)
This study aims to examine the effect of accountability and transparency on performance-based budgeting. In this study the sample used is the Regional Government Organization (OPD) of Bengkulu Province. Tests conducted on the data that was obtained from the questionnaire of 68 respondents. The technique used to test this research hypothesis is F-test and t-test with 5% significant level. This study found that accountability and transparency positively influence on performance-based budgeting. The results of this study provide an important contribution for the government to pay more attention at accountability and transparency in budgeting planning in order to achieve effective and efficient performance.